Detailed Li-ion battery characterization model for economic operation. (March 2020) - Gonzalez-Castellanos, Alvaro; Pozo, David; Bischi, Aldo
Highlights: A detailed linear model for Li-ion batteries is provided. The developed model provides technical limits for the battery based on its state of energy and requested power. Expressions for the efficiencies dependent on the operation point are presented as well. The proposed model can be adapted for the implementation of diverse energy storage applications. Abstract: The rapid adoption of Li-ion batteries in electric vehicles, merchant storage applications, and as providers of ancillary services to the electric grid, requires the development of tractable and accurate models for their reliable operation. For such operations, it is common practice to use generic and ideal storage mathematical models, i.e., models in which the storage efficiency and power limits are considered constant; resulting in a possible miscalculation of the flexibility and profit gained from the use of storage units. To promote a more accurate characterization of energy storage operation, we propose a linear model representing the variable efficiencies and power limits; for both battery charging and discharging processes. Based on a battery equivalent circuit model, we analyze the non-convex behavior of the power limits and efficiencies. Through the use of a methodology for the piece-wise approximation of a concave function, we derive a linear model that characterizes both the battery power limits and the efficiencies as affine functions of the level of stored energy and the power charged/discharged. The proposed linear model is compared with a generic one under a centralized economic dispatch and merchant storage operation. A reliability analysis of the use of generic storage models is presented, highlighting the impact on the system's flexibility derived from the simplifications present in this model. The use of the proposed model guarantees the feasibility of the battery scheduling, preventing additional compensation costs for both the system operator and merchant investor.